Non‐ and semipolar AlInN one‐dimensionally lattice‐matched to GaN for realization of relaxed buffer layers for strain engineering in optically active GaN‐based devices. Issue 1 (28th September 2015) - Buß, E. R.; Horenburg, P.; Rossow, U.; Bremers, H.; Meisch, T.; Caliebe, M.; Scholz, F.; Hangleiter, A.
Abstract: In this contribution, we demonstrate that for non‐ and semipolar AlInN one‐dimensionally lattice‐matched to GaN, controlled relaxation in different in‐plane directions of the growth surface can be induced. All of our samples were grown on ( 11 22 ‾ ) GaN templates on patterned r ‐plane sapphire as well as on m ‐oriented 6H‐SiC substrates and free‐standing pseudo‐bulk GaN substrates. The InN mole fraction of the Al 1 − x In x N is varied from 18% up to 28% corresponding to one‐dimensional lattice matching in various in‐plane directions of the growth surface. By controlling the composition as well as the thickness, we realized one‐dimensional relaxation of the AlInN layers along the nonlattice‐matched direction. This opens new perspectives for strain and polarization engineering in optically active layers grown subsequently and gives new possibilities to design high indium‐containing GaInN quantum well structures for efficient long wavelength light emitters.